Ketertarikan Serangga Terhadap Berbagai Jenis Warna Dan Ketinggian Perangkap Pada Tanaman Cabai Besar - Saupi, Muhammad; Rosa, Helda Orbani; Marsuni, Yusriadi (www.ulm.ac.id, 2025)
Color traps are one way to control insects around plants. This research aims to determine the type of color and height of the trap on insect attraction to chili plants in 2 generative phases and vegetative phase. This research took place in Bentok Darat Village, Bati-Bati District, Tanah Laut Regency, South Kalimantan Province. The method used was (RAL) with 2 factors and 3 repetitions. The first color factor is W1: Yellow, W2: Green, W3: Red and the second factor is the height of T1: 30 cm, T2: 60 cm and T3: 90 cm. The results of this research were that yellow traps had the highest number of insect catches, namely 1,634 and at a height of 30 cm, yellow traps had the highest number of catches, 362. From this research, the total number of insect catches obtained was 3,676 individuals. In the vegetative phase there were 1,629 insects and in the generative phase there were 2,047 insects.